2017
DOI: 10.1590/1983-21252017v30n113rc
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Regrowth of Neem After Cutting in Saline - Sodic Soil Treated With Organic Inputs

Abstract: -Soil salinity and sodicity are global problems since both promote the physical, chemical and biological degradation of soil, jeopardising the productive capacity of agricultural fields. Inorganic correctives or organic inputs are applied as an attempt to reduce the problem, alongside the use of salt-tolerant plants. This study aimed at evaluating the effects of organic inputs on the growth of neem (Azadirachta indica) strains in saline-sodic soil after cutting. Treatments were arranged in a randomised block d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 15 publications
2
7
0
3
Order By: Relevance
“…Based on this Figure, Cavalcante et al (2010) also observed increased root growth with the application of biofertilizer in guava seedlings. The superiority of the biofertilizer rich ( _._ ) may be due to a higher concentration of nutrients, such as calcium, magnesium and potassium, in its chemical composition (RODRIGUES et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this Figure, Cavalcante et al (2010) also observed increased root growth with the application of biofertilizer in guava seedlings. The superiority of the biofertilizer rich ( _._ ) may be due to a higher concentration of nutrients, such as calcium, magnesium and potassium, in its chemical composition (RODRIGUES et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…According to Rodrigues et al (2017), although biofertilizers increase the electrical conductivity of substrates, it also increase plant growth and biomass production.…”
Section: Resultsmentioning
confidence: 99%
“…The morphological parameters of the seedlings and their relationships used in the evaluating the results were: height of aerial part (HAP), stem diameter (SD), Number of leaves (NL), Area Leaf (AL) and Root Length (RH) how did it proceed [18], in Indian neem seedlings (Azadiracta indica A. Juss), [26] in the seedlings of neem [27] in the culture of the yallow passion fruits [28].…”
Section: Variables Analyzed At the End Of The Experimentsmentioning
confidence: 99%
“…According to Ayers and Westcot [30], yellow passion fruit is considered to be sensitive to the effects of salts with waters that offer moderate (ECw > 2.50 dS m -1 ) or severe (ECw > 3.0 dS m -1 ) restrictions. However, according to Rodrigues et al [27], these organic inputs, despite providing an increase in the electrical conductivity of the substrate, stimulate the growth and production of vegetal biomass. The results are in agreement with [31], [29], and [12] when they noticed increase in the concentration of salts of the soil with irrigation of waters with increasing salinity.…”
Section: Summary Of Mean Squares and Diagnosis Of Significance Regardmentioning
confidence: 99%
“…De acordo com Moreira et al (2012), esta espécie tem despertado a atenção e seus produtos têm sido cada vez mais utilizados na área de produção vegetal. Em sua área de ocorrência natural, esta espécie é conhecida especialmente por suas propriedades medicinais e inseticidas, bem como pela resistência e a dureza da sua madeira (RODRIGUES et al, 2017).…”
Section: Uma Das Espécies Que Tem Sido Utilizada Na Arborização Urbanunclassified